Renan ante Lamennais, Ortega ante Baroja y los usos de la perspectiva - de Salas Ortueta, Jaime (Logos. Anales del Seminario de Metafísica, 2002)
One of Ortega y Gasset’s more important contributions was his theory and methodological use of the concept of perspective. Clearly he´s indebeted to Nietzsche on this issue, but it can also be surmised that Renan was also important in this issue at the time that Ortega was preparing Meditaciones del Quijote. The article compares Renan’s criticism of Lamennais with Ortega’s interpretation of Pío Baroja focusing not only on the paralelism of their criticisms of established and prominent personalities of their intelectual community, but also on the underlying understanding of cultural practice.